Analysis of Illegal Gold Mining (PETI) Impact on The Environment with TDS, TSS, Mercury and Cyanide Parameters in Water and Sediment of Cikaniki River - Erusani, Awang Silvan; Arofah*, Nurmaya; Sofatunida, Sofatunida; Fauzi, Talitha Hasna; Jabbar, Muhammad Andi (Graduate School of Universitas Syiah Kuala, 2025)
Gold production from artisanal mining extraction reaches 120 tons annually, providing significant environmental and economic impacts for the community. The processing method used triggers environmental pollution, because it produces tailings in the form of metal mercury and cyanide. This research was conducted at the location of post Illegal gold mining (PETI), although PETI activities have been disciplined, but based on the characteristics of mercury which is difficult to dissolve in water, easily binds to suspended solids and easily deposited to the bottom of the waters, can pollute river sediments. The purpose of the study was to determine the levels of Total Dissolved Solid (TDS), Total Suspended Solid (TSS), mercury and cyanide in the Cikaniki River Watershed, based on Government Regulation No. 22 of 2021. The purposive sampling method was used in determining the sampling location at 3 observation stations for surface water and sediment, namely station 1 area where is former gold processing. Station 2 river body where former PETI produces mercury waste, station 3 is a place where there is no gold processing. TDS and TSS measurements using the gravimetric method, mercury and cyanide levels using ICP-OES. The results of laboratory sediment analysis of 3 observation location in Cisarua Village, Curug Bitung Village, and Lukut Village, for the TDS and TSS parameters, mercury was detected at the highest level at point 3 in Lukut Village. Luku Village is the most downstream location of the Cikaniki River which is located very far form the peoples gold processing site. This concludes that after PETI activities occur, the distribution of mercury (Hg) waste spread to the most downstream areas of the Cikaniki River is always present even though its presence is still below environmental quality standards.